PREPARATION OF EDUCATIONAL GAMES THAT ARE USED IN THE STUDY OF THE VERB WORD CATEGORY - Mirzayeva Dilrabo Ulug‘bekovna (Лучшие интеллектуальные исследования, 2024)
Annotation: getting to know the methods of teaching words related to the verb category to students in the elementary grades. Get acquainted with educational games through the article.